Implementation success of internet-based electronic commerce for small- and medium-sized enterprises in Australia - Chong, Sandy; Pervan, Graham; Bauer, Christian (Kranj Mioderna Organizacija, 2001)
This study surveys the perceptions and experience of Australian small- and medium-sized enterprises (SMEs) in the adoption and implementation of Internet-based Electronic Commerce. Employing Rogers (1995) model of innovation diffusion as the framework and considering Electronic Commerce (EC) as a form of new innovation, we analyse factors affecting EC implementation success. With a sample of 71 small businesses in Australia, preliminary results show that respondents' perception of the attributes of Internet-based EC are pre-dominantly positive. However, a further analysis was carried out regressing overall satisfaction of EC implementation on the five attributes of innovation. It was found that only 3 characteristics - perceived relative advantage, compatibility and complexity to make a significant contribution to the implementation success of Internet-based EC adoption.